2018
DOI: 10.1111/jcmm.13480
|View full text |Cite
|
Sign up to set email alerts
|

Increased free Zn2+ correlates induction of sarco(endo)plasmic reticulum stress via altered expression levels of Zn2+‐transporters in heart failure

Abstract: Zn2+‐homoeostasis including free Zn2+ ([Zn2+]i) is regulated through Zn2+‐transporters and their comprehensive understanding may be important due to their contributions to cardiac dysfunction. Herein, we aimed to examine a possible role of Zn2+‐transporters in the development of heart failure (HF) via induction of ER stress. We first showed localizations of ZIP8, ZIP14 and ZnT8 to both sarcolemma and S(E)R in ventricular cardiomyocytes (H9c2 cells) using confocal together with calculated Pearson's coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…In contrast, CALU , ST3GAL4 , CRTC2 , SLC28A2 , and COMMD1 were downregulated. As has been previously reported in other systems, our data support a role for excess dietary Zn in the intestine in activating endoplasmic reticulum (ER) stress and signaling. Calumenin ( CALU ) is a calcium‐binding protein localized in the ER involved in functions including protein folding and sorting, and regulates the activity of SERCA2a and of the ryanodine receptor .…”
Section: Resultssupporting
confidence: 90%
“…In contrast, CALU , ST3GAL4 , CRTC2 , SLC28A2 , and COMMD1 were downregulated. As has been previously reported in other systems, our data support a role for excess dietary Zn in the intestine in activating endoplasmic reticulum (ER) stress and signaling. Calumenin ( CALU ) is a calcium‐binding protein localized in the ER involved in functions including protein folding and sorting, and regulates the activity of SERCA2a and of the ryanodine receptor .…”
Section: Resultssupporting
confidence: 90%
“…Of note, both skeletal and cardiac muscle catabolism occur in pancreatic cancer mouse models 48 and patients 11 . In the heart, ZIP14 is expressed at relatively high levels 49 , and is increased after doxorubicin treatment 50 , resulting in increased intracellular zinc levels and induction of sarcoplasmic reticulum stress 51 .…”
Section: Inter- and Intracellular Mediators Of Skeletal And Heart Musmentioning
confidence: 99%
“…Moreover, the zinc transporter Zip14 is closely related to inflammation and production of proinflammatory cytokines (Aydemir et al, 2012;Eizirik et al, 2012;Troche et al, 2016). Zip14 is also expressed in cardiac tissues and located in the plasma membrane, which promotes extracellular zinc into the cytosol and increases the concentration of zinc in the cytosol (Taylor et al, 2007;Olgar et al, 2018a). We observed higher expression levels of in cardiomyocytes were increased compared with the SHAM group.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the zinc trafficking and the activity of the Zip14 transporter are important for adapting to the ERSassociated chronic metabolic disorders, and the Zip14mediated transport of zinc is necessary for adapting ERS (Kim et al, 2017). Olgar et al (2018a) also reported that Zn 2+ correlates the induction of ERS through altering expressions of Zn 2+ -transporter, Zip14, in heart failure. Therefore, there might be a correlation between the Zip14 and the ERS.…”
Section: Introductionmentioning
confidence: 97%